Extracellular vesicles in neuroblastoma: role in progression, resistance to therapy and diagnostics - Dhamdhere, Mayura R.; Spiegelman, Vladimir S. (Frontiers in Immunology, 2024)
Neuroblastoma (NB) is the most common extracranial solid pediatric cancer, and is one of the leading causes of cancer-related deaths in children. Despite the current multi-modal treatment regimens, majority of patients with advanced-stage NBs develop therapeutic resistance and relapse, leading to poor disease outcomes. There is a large body of knowledge on pathophysiological role of small extracellular vesicles (EVs) in progression and metastasis of multiple cancer types, however, the importance of EVs in NB was until recently not well understood. Studies emerging in the last few years have demonstrated the involvement of EVs in various aspects of NB pathogenesis. In this review we summarize these recent findings and advances on the role EVs play in NB progression, such as tumor growth, metastasis and therapeutic resistance, that could be helpful for future investigations in NB EV research. We also discuss different strategies for therapeutic targeting of NB-EVs as well as utilization of NB-EVs as potential biomarkers.